3D Food Printing: A Taste of the Future. Issue 3 (22nd June 2015) - Lin, Clarice
Abstract One of the core competencies in the Institute of Food Technologists (IFT) education standards is for students to achieve competency in communication skills (that is, oral and written communication, listening, interviewing, and so on). According to the IFT guidelines, by the time students graduate, they should not only be able to search for and condense information, but also be able to "communicate technical information to a nontechnical audience." The Education, Extension and Outreach Division of IFT sponsors a writing competition for undergraduate students to bring attention to and promote the development of communication skills. It has been shown that employees/entry‐level scientists who can communicate technical and nontechnical concepts succinctly will be in a better position to achieve management status after entering the work force. Monetary prizes are awarded to the authors of the top 3 papers. A revised version of the winning entry is published in the Journal of Food Science Education for dissemination to a worldwide audience.